Analisis Monitoring Pembiayaan Mudharabah dalam Mengurangi Resiko NPF pada Bank Muamalat KCP Sukaramai Medan - Muhammad Ilham; Sugianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the monitoring and mitigation of NPF risk in mudharabah financing at Bank Muamalat KCP Sukaramai Medan. The research method used is a descriptive qualitative approach with data collection through observation, interviews and analysis of related documents. The analysis results show that Bank Muamalat has implemented various risk mitigation strategies such as financing restructuring, monitoring partners, and portfolio diversification to reduce NPF risk. The significant decline in the NPF level after implementing risk mitigation policies shows the effectiveness of this strategy in maintaining bank financial stability. In conclusion, the monitoring analysis of mudharabah financing at Bank Muamalat KCP Sukaramai Medan proves the importance of risk mitigation strategies in managing NPF risk and ensuring the sustainability of sharia banking business.